Environmental Buddhism, Engaged Buddhism: an insight to the Thai Environmental Buddhist movement (2015)
Thai society is experiencing an environmental crisis that manifests itself in the rapid degradation of its natural resources, mainly caused by exploitation dynamics. Faced with this situation, Buddhist monks have manifested themselves in different ways, acquiring a social, political and environmental commitment, in order to find solutions to the environmental crisis. One of the manifestations has been the creation of the Thai Environmental Buddhist Movement, which is based on Buddhist principles to carry out actions that contribute to the protection and conservation of the environment. The objective of this article is to explore the role of this movement in Thailand, based on "Engaged Buddhism" and "Environmental Buddhism", which are the currents of thought that allow the movement to emerge and its current existence. This will explain the relationship between Buddhism and the environment, in order to contribute to the debate on the union of these two aspects and their impact today.